2005
DOI: 10.1128/jvi.79.24.15027-15037.2005
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Induction of AP-1 and Interleukin 6 during Primary Infection Mediated by Multiple Mitogen-Activated Protein Kinase Pathways

Abstract: Kaposi's sarcoma is an angioproliferative disseminated tumor of endothelial cells linked to infection with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 76 publications
5
138
0
Order By: Relevance
“…The requirement for IL-6 during KSHV infection is well documented [30][31][32][33][34][35][36][37][38], but the role of GADD45B may be more nuanced. While we demonstrated that it escapes host shutoff during lytic KSHV infection and appears important for viral reactivation in the iSLK.219 model, GADD45B expression is repressed by viral miRNAs during latency to avoid its cell cycle arrest and pro-apoptotic functions [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement for IL-6 during KSHV infection is well documented [30][31][32][33][34][35][36][37][38], but the role of GADD45B may be more nuanced. While we demonstrated that it escapes host shutoff during lytic KSHV infection and appears important for viral reactivation in the iSLK.219 model, GADD45B expression is repressed by viral miRNAs during latency to avoid its cell cycle arrest and pro-apoptotic functions [73].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 expression is required for survival of B cells infected with KSHV, and the virus engages a number of strategies to drive production of this cytokine [30][31][32][33][34][35][36][37][38]. The IL-6 mRNA is directly refractory to SOX cleavage and thus remains robustly induced during host shutoff due to the presence of a specific 'SOX resistance element' (SRE) [26,29].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of EBV latency by BRLF1 is prevented by inhibitors of p38 or JNK (Adamson et al, 2000). Another human herpesvirus, Kaposi's sarcoma-associated herpesvirus (HHV-8), has been reported to activate the ERK, p38 and JNK MAP kinase pathways during primary infection (Naranatt et al, 2003;Xie et al, 2005), and the activation of these pathways is essential for HHV-8 infection (Pan et al, 2006). Inhibitors of all three MAP kinase pathways reduce HHV-8 infectivity by reducing lytic replication and, as a result, the yield of infectious virions (Pan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These signaling events mediate several functions, such as activation of the cytoskeleton, endocytosis, gene expression, cell motility, attachment, the cell cycle, cell growth, apoptosis, and differentiation (10,11,19,32,48). During early times of infection, KSHV induces integrin-mediated FAK phosphorylation that is followed by the activation of a variety of focal adhesion-associated signal molecules, such as Src, PI-3K, Rho GTPases (RhoA, Rac, and Cdc42), and Diaphanous 2 (Dia2), as well as several downstream effector molecules, such as AKT, Ezrin, PKC-, MEK, ERK1/2, NF-B, and p38MAPK (4,18,30,35,37,39,41,42,47,49,(50)(51)(52)(53)(55)(56)(57) (Fig. 3).…”
Section: Kshv Induces Host Cell Preexisting Signal Molecules Early Dumentioning
confidence: 99%